Impact of Identity Politics on Security and Stability in Medan - Muhammad Iqbal Zubaidi (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to investigate the influence of identity politics on political stability and security in Indonesia. This research uses a literature review method to collect and analyse various previous studies on identity politics, political stability and security in Indonesia. Data were analysed qualitatively to identify patterns, trends and relationships between identity politics variables and political stability and security. The results of the analysis show that identity politics has a significant influence on political stability and security in Indonesia. Religious, ethnic and regional-based political identification is an essential factor influencing political and security dynamics in this country. Political conflicts rooted in differences in identity often trigger political and security tensions that have a negative impact on state stability. Based on the analysis results, it can be concluded that identity politics significantly impacts political stability and security in Indonesia. A better understanding of the dynamics of identity politics can help formulate more effective policies to maintain political stability and security in the country.